2018
DOI: 10.36778/jesya.v2i1.35
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Faktor Ekonomi Makro Terhadap Stock Return Pada Indeks Saham LQ45

Abstract: Penelitian ini dilakukan untuk menganalisa pengaruh variabel-variabel ekonomi makro, yaitu inflasi, suku bunga, nilai tukar, harga minyak dunia, produk domestik bruto, ekspor, dan impor terhadap stock return perusahaan yang terdaftar di indeks saham LQ45. Sampel dari penelitian ini adalah 79 perusahaan yang pernah terdaftar di LQ45 selama periode Februari 2012 sampai dengan Januari 2017. Metode analisis data yang digunakan adalah regresi panel. Hasil penelitian menunjukkan bahwa inflasi, suku bunga, nilai tuka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 10 publications
1
7
1
10
Order By: Relevance
“…These results follow the results of research conducted by (Asmara, 2018), (Ahmad & Ramzan, 2016), (Andyani, K. W., & Mustanda, 2018), (Candy, & Winardy, 2019), (Chandrashekar, R., Sakthivel, P., Sampath, T., & Chittedi, 2018), (Eldomiaty et al, 2019), (Hidayat, L. R., & Azis, 2017), (Ilmi, 2017), (Innocent et al, 2018), (Jamaludin et al, 2017), (Ismail et al, 2016), (Khan, 2019), (Nkoro & Uko, 2016), (Sari, 2019) and Restiawan dan Asytuti (2020) state that inflation has a negative effect to stock returns. states that inflation harms stock returns.…”
Section: C) Relationship Of Gross Domestic Product With Lq45 Indexsupporting
confidence: 90%
See 1 more Smart Citation
“…These results follow the results of research conducted by (Asmara, 2018), (Ahmad & Ramzan, 2016), (Andyani, K. W., & Mustanda, 2018), (Candy, & Winardy, 2019), (Chandrashekar, R., Sakthivel, P., Sampath, T., & Chittedi, 2018), (Eldomiaty et al, 2019), (Hidayat, L. R., & Azis, 2017), (Ilmi, 2017), (Innocent et al, 2018), (Jamaludin et al, 2017), (Ismail et al, 2016), (Khan, 2019), (Nkoro & Uko, 2016), (Sari, 2019) and Restiawan dan Asytuti (2020) state that inflation has a negative effect to stock returns. states that inflation harms stock returns.…”
Section: C) Relationship Of Gross Domestic Product With Lq45 Indexsupporting
confidence: 90%
“…For the interest rate variable, (Candy, & Winardy, 2019) states that interest rates positively affect stock returns. Different results were obtained by research (Asmara, 2018), stating that interest rates harm stock returns.…”
Section: Introductionmentioning
confidence: 99%
“…Economic growth has no significant effect on stock returns. The results of this study contradict Candy & Winardy (2018). The results showed that inflation, interest rates, exchange rates, gross domestic product, exports, and imports have a significant effect on stock returns.…”
Section: The Multiple Linear Regression Equation Is As Followscontrasting
confidence: 89%
“…Research by Candy & Winardy (2018) regarding the effect of inflation and exchange rates on stock returns, there is a significant long-term relationship between returns and market inflation, however, there is no significant short-term relationship. These results also show a significant long-term and short-term relationship between market returns and exchange rates (Kwofie & Ansah, 2018).…”
Section: Economic Growthmentioning
confidence: 99%
“…Macroeconomics or often called macroeconomics is one part of the economic field that discusses all economic problems (Jusman & Puspitasari, 2019;Giffarina, 2021). Fields of macroeconomic studies include inflation, interest rates, exchange rates, imports, exports, world oil prices, and others (Mota-Hernandez et al, 2014;Salim, 2016;Candy & Winardy, 2018;Kennedy & Hayrani, 2018). Macroeconomic studies are explained in detail based on the economic problems of a country, therefore the topics discussed tend to be more numerous and complex.…”
Section: Introductionmentioning
confidence: 99%